Leukocyte-Rich versus Leukocyte-Poor Platelet-Rich Plasma for the Treatment of Knee Osteoarthritis: A Double-Blind Randomized Trial. Issue 3 (March 2022) - Di Martino, Alessandro; Boffa, Angelo; Andriolo, Luca; Romandini, Iacopo; Altamura, Sante Alessandro; Cenacchi, Annarita; Roverini, Veronica; Zaffagnini, Stefano; Filardo, Giuseppe
Background: Platelet-rich plasma (PRP) is gaining large interest in clinical practice as a minimally invasive injective treatment for knee osteoarthritis (OA). Different preparation methods are available, and the presence of leukocytes, deemed detrimental in some preclinical studies, is one of the most debated aspects regarding PRP efficacy. Purpose: To compare the safety and effectiveness of leukocyte-rich PRP (LR-PRP) and leukocyte-poor PRP (LP-PRP) for the treatment of knee OA. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 192 patients with symptomatic knee OA (Kellgren-Lawrence grade 1-3) were randomly allocated to 3 weekly injections of LR-PRP or LP-PRP. LP-PRP was obtained with a filter for leukodepletion. LR-PRP and LP-PRP were divided into aliquots of 5 mL, with a mean platelet concentration of 1146.8 × 10 9 /L and 1074.9 × 10 9 /L and a mean leukocyte concentration of 7991.4 × 10 6 /L and 0.1 × 10 6 /L, respectively. Patients were evaluated at baseline and thereafter at 2, 6, and 12 months for the primary outcome, the International Knee Documentation Committee (IKDC) subjective score; and for secondary outcomes, the Knee injury and Osteoarthritis Outcome Score (KOOS) subscales, EuroQol–visual analog scale (EQ-VAS), and Tegner score. Results: No differences between groups were observed in terms of absolute values or improvement of the clinical scores across all follow-up intervals. The mean IKDC subjective score at baseline and 12 months improved from 45.6 to 60.7 in the LR-PRP group as compared with 46.8 to 62.9 in the LP-PRP group ( P = .626). No severe adverse events were described in either group, although 15 mild adverse events (knee pain or swelling) were reported: 12.2% for LR-PRP and 4.7% for LP-PRP ( P = .101). No statistically significant difference was also found between LR-PRP and LP-PRP in terms of failures (7.8% vs 3.5%, P = .331). Conclusion: This double-blind randomized trial showed that 3 intra-articular LR-PRP or LP-PRP injections produced similar clinical improvement in the 12 months of follow-up in patients with symptomatic knee OA. Both treatment groups reported a low number of adverse events, without intergroup differences. The presence of leukocytes did not significantly affect the clinical results of PRP injections. Registration: NCT02923700 (ClinicalTrials.gov identifier).